The Responsibility of Land Deed Making Officials and Notaries in Illegal Land Rights Transfer (Case Study of Nirina Zubir Land Mafia) - Anami, Mulan Kasisty; Hadi, Syamsul (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
The involvement of rogue Land Deed Officials (PPAT) and Notaries in illegal land title transfers, exemplified by the case of Nirina Zubir, constitutes a severe breach of their Profession Code of Ethics and professional oath. This highlights their failure to perform the principle of due diligence, as it is exploited by involving themselves in land mafias practice. The professional duty to act with honesty, integrity, diligence, independence, and impartiality, mandated by the Code of Ethics, the Notary Public Law (UUJN), and Regulation on the Office of the PPAT is violated when an authentic deed is issued based on forged documents or false identities. Such actions directly cause significant material losses and trigger a Tort (Perbuatan Melawan Hukum/PMH) under Article 1365 of the Civil Code. The consequences of these ethical violations are layered, encompassing professional disciplinary sanctions (ranging up to dishonorable discharge by the Notary Honorary Council or the PPAT Honorary Assembly), along with potential civil and criminal liability. This makes it a crucial issue demanding rigorous legal and ethical enforcement to restore the profession's integrity and ensure legal certainty in land affairs.